New perspectives on public services : place and technology - Pollitt, Christopher (Oxford University Press, 2012)
Despite their immense importance for many aspects of public service management, the specific features of places have been largely ignored in recent public management literature. Technologies have received much more attention, but mainly within the specific field of e-government. In this book Christopher Pollitt puts together a powerful and engagingly-written case for paying much more attention both to place and to technological change, and the interactions betweenthem. The book synthesizes theories and concepts from a range of disciplines and focuses them on the many ways in which public servi.